2014
DOI: 10.1371/journal.pone.0106010
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Leukemia Inhibitory Factor (LIF) during the Early Stage of Optic Nerve Regeneration in Zebrafish

Abstract: Fish retinal ganglion cells (RGCs) can regenerate their axons after optic nerve injury, whereas mammalian RGCs normally fail to do so. Interleukin 6 (IL-6)-type cytokines are involved in cell differentiation, proliferation, survival, and axon regrowth; thus, they may play a role in the regeneration of zebrafish RGCs after injury. In this study, we assessed the expression of IL-6-type cytokines and found that one of them, leukemia inhibitory factor (LIF), is upregulated in zebrafish RGCs at 3 days post-injury (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 59 publications
(86 reference statements)
3
20
1
2
Order By: Relevance
“…Thus, it was unexpected to see only LIF, and not also IL-6, mRNA increase with CCL2 overexpression. We also assayed the expression of two known gp130 cytokine/STAT3-dependent genes, galanin and GAP-43 (Ogai et al, 2014; Qiu et al, 2005; Rao et al, 1993; Zigmond, 2012) and found that their expression remained unchanged following CCL2 overexpression. Although initially surprising, this may indicate that LIF-induced gene expression requires more than a 4-fold increase in the cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was unexpected to see only LIF, and not also IL-6, mRNA increase with CCL2 overexpression. We also assayed the expression of two known gp130 cytokine/STAT3-dependent genes, galanin and GAP-43 (Ogai et al, 2014; Qiu et al, 2005; Rao et al, 1993; Zigmond, 2012) and found that their expression remained unchanged following CCL2 overexpression. Although initially surprising, this may indicate that LIF-induced gene expression requires more than a 4-fold increase in the cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, porcine retinal explants are mostly used to analyze neuroprotection and cell survival, rather than neurite outgrowth MartinezFernandez;de la Camara et al 2014;Taylor et al 2014;Bell et al 2016). Regarding anamniote models, retinal explants harvested from goldfish or zebrafish have also been used to test the putative effect of both intrinsic and extrinsic factors on RGC outgrowth/regeneration, albeit to a more limited extend (Nusetti et al 2005;Veldman et al 2007Veldman et al , 2010Cubillan et al 2012;Ou et al 2012;Ogai et al 2014). To culture fish retinal explants, retinas are chopped into small squares and transferred to poly-L-lysine-coated well plates.…”
Section: Ex Vivo Tissue Explant Studies In Other Vertebratesmentioning
confidence: 99%
“…To culture fish retinal explants, retinas are chopped into small squares and transferred to poly-L-lysine-coated well plates. After an incubation period of 1-4 days, the number of neurites, their length and/or density can be quantified (Becker and Becker 2002;Becker et al 2004;Veldman et al 2007Veldman et al , 2010Elsaeidi et al 2014;Ogai et al 2014;Welte et al 2015;Van Houcke et al 2017). …”
Section: Ex Vivo Tissue Explant Studies In Other Vertebratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, fish central nervous system (CNS) neurons can regenerate even after nerve transection, whereas mammalian CNS neurons cannot [17][18][19]. We have previously cloned RAGs from the axotomized zebrafish visual system, including the retina, and found that they are largely classified into two groups: one that displays anti-oxidant or anti-apoptotic activity and another that displays neurite outgrowth activity [19][20][21][22][23][24][25][26]. The former type can be induced at an early stage of nerve regeneration immediately after optic nerve injury, whereas the latter can typically be induced at a later stage of nerve regeneration [19].…”
Section: Introductionmentioning
confidence: 99%